Pester Power: The Strategic Use of Child Model in Advertising - Maiti, Srabani Roy (Indian Journal of Marketing, 2012)
Modern advertising is more of a psychological process. It has become the most convenient route to reach the consumer's mind. Modern advertisements use children to give an emotional undertone to the products, suggesting the audience an element of familiarity. This trend is compatible with the changes occurring in the traditional family structure because of the forces of globalization. The modern family has become child-centric in its lifestyle. The pester power of children is well-acknowledged by marketers. Companies across categories like healthcare, personal care, newspapers and even computers have realized that the best way to enter homes is through children. Furthermore, it is the best way to hook a customer early in his life or to catch-them young. Now-a-days, advertisers are using psychoanalytical techniques to influence consumer's mind, which is known as psychographics or 'life-style' approach to selling. From the ethical point of view too, there is no harm in doing so, unless and until they are not harming the sentiment and economic infrastructure of the family. In this paper, the arguments that can be put forward are that the use of child models in modern advertising has indeed become a very effective tool to influence the consumers as well as to sell the products. And if used effectively and ethically, it can work wonders for the advertisers. The methodology used for the research was content analysis of the products, sample survey through a close ended questionnaire, and interviews of different persons.